Antimicrobial Resistance of Streptococcus pneumoniae Strains Isolated from Various Clinical Specimens - Berktaş, Mustafa; Parlak, Mehmet; Çıkman, Aytekin; Güdücüoğlu, Hüseyin (Fırat University, 2013)
Objective: Streptococcus pneumoniae is an important cause of morbidity and mortality because of the increasing antibiotic resistance. In this study we aimed to determine resistance rates of Streptococcus pneumoniae strains to various antibiotics. Materials and Methods: A total of 80 S.pneumoniae strains isolated from various clinical specimens were examined. Identification and antibiotic susceptibility testing of microorganisms thought to be S.pneumoniae with conventional methods was performed by BD Phoenix automated microbiology system (Becton Dickinson, USA) and its panels of streptococci. Antibiotics were evaluated based on manual of Clinical and Laboratory Standards Institute (CLSI) 2010 drug groupings. Results: Antibiotic resistance rates of S.pneumoniae strains were 33% to erythromycin, 25% to tetracycline, 21% to trimethoprim-sulfamethoxazole, 14% to clindamycin, 8% to penicillin, 8% to meropenem, 6% to cefepime, 5% to chloramphenicol, 5% to amoxicillin, %5 to telithromycin, 4% to levofloxacin, 4% to moxifloxacin and 3% to cefotaxime, respectively. All strains were sensitive to linezolid and vancomycin. Conclusion: Antibiotic resistance rates of the antibiotics recommended for the treatment of infections caused by S. Pneumonie were found low.

Amaç: Giderek artan direnç oranlarıyla önemli bir mortalite ve morbidite nedeni olan Streptococcus pneumoniae suşlarının çeşitli antibiyotiklere karşı direnç oranlarının belirlenmesi amaçlandı. Gereç ve Yöntem: Çeşitli klinik örneklerden izole edilen toplam 80 S.pneumoniae suşu incelendi. Konvansiyonel yöntemlerle S.pneumoniae olduğu düşünülen mikroorganizmaların identifikasyonu ve antibiyotik duyarlılık testlerinde BD Phoenix otomatize mikrobiyoloji sistemi (Becton Dickinson, USA) ile bu sisteme ait streptokok panellerinden yararlanıldı. Antibiyotikler, Clinical and Laboratory Standards Institute (CLSI)'nin 2010 klavuzunda belirtmiş olduğu ilaç gruplamaları kriter alınarak değerlendirmeye alındı. Bulgular: S.pneumoniae suşlarında eritromisine %33, tetrasikline %25, trimetoprim-sulfametoksazole %21, klindamisine %14, penisiline %8, meropeneme %8, sefepime %6, kloramfenikole %5, amoksisiline %5, telitromisine %5, levofloksasine %4, moksifloksasine %4 ve sefotaksime %3 oranında direnç saptandı. Tüm suşların linezolid ve vankomisine duyarlı olduğu belirlendi. Sonuç: S.pneumoniae'nın etken olduğu enfeksiyonların tedavisi için önerilen antibiyotiklere direnç oranlarımız düşük olarak bulunmuştur.
Klinik Örneklerden İzole Edilen Streptococcus pneumoniae Suşlarının Çeşitli Antibiyotiklere Direnci